Lima Strategi untuk Meningkatkan Kualitas Pembelajaran di SMA Budi Mulia Karawang: Penelitian - Agus Purwanto; Farhan Amrilah Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Abstract With the education report card, the problems related to the quality of education in schools are clearly visible. The problems that currently exist at SMA BUDI MULIA that need to be improved are: quality of learning, numeracy skills, PMM usage activities, With the independent curriculum being a challenge in itself in order to direct diverse human resources in schools and mobilize learning communities. In improving the quality of education in schools, based on the education report card improvement program, the author created five mentoring programs with the term